3D Graphene-based macro-mesoporous frameworks as enzymatic electrodes. (July 2019) - Shen, Ling; Ying, Jie; Ren, Lei; Yao, Yao; Lu, Yi; Dong, Ying; Tian, Ge; Yang, Xiao-Yu; Su, Bao-Lian
Abstract: An efficient method was developed to fabricate three-dimensional (3D) graphene-based nanomaterials with hierarchical macro-mesoporous structures as novel enzymatic electrode materials. The 3D continuously interconnected macropores were generated by hydrothermal self-assembly of graphene oxide sheets to form 3D graphene-based frameworks, and uniform mesopores on the surface of graphene frameworks were obtained by replicating the previously synthesized mesoporous silica. Due to the integration of macropores that can promote the efficiency of mass transfer, and mesopores that can facilitate enzyme immobilization and electron transfer, the unique 3D graphene-based macro-mesoporous frameworks with narrow mesopore size distribution, large surface area and high electrical conductivity can be applied as an excellent platform to immobilize glucose oxidase as enzymatic electrodes, displaying enhanced glucose-sensing properties. This approach can be utilized to fabricate various 3D hierarchical macro-mesoporous nanomaterials for application in a broad range of sensors, supercapacitors, batteries and catalysis. Graphical abstract: Image 1 Highlights: 3D graphene-based frameworks with hierarchical macro-mesoporous structures are synthesized. Frameworks are applied as platforms to immobilize glucose oxidase as enzymatic electrodes. The obtained enzymatic electrodes display enhanced glucose sensing properties.